2001
DOI: 10.1155/2001/296752
|View full text |Cite
|
Sign up to set email alerts
|

Sabot Front Borerider Stiffness vs. Dispersion: Finding the Knee in the Curve

Abstract: In the design of armor piercing, fin-stabilized, discarding sabot projectiles, the radial stiffness of the sabot front borerider has a significant impact on the projectile's dispersion and is, therefore, an important design consideration. Whether designing a new projectile or trying to improve an existing design, projectile designers can achieve front borerider stiffness without understanding its affect on dispersion characteristics. There is a knee in the stiffness vs. dispersion curve at which a change in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Gun-projectile interaction has been investigated through large amount of researches. Experimental setups, analytical and finite element models have been developed to simulate the gun-projectile interaction and to examine the sensitivity of parameters on the dispersion [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gun-projectile interaction has been investigated through large amount of researches. Experimental setups, analytical and finite element models have been developed to simulate the gun-projectile interaction and to examine the sensitivity of parameters on the dispersion [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…The sabot front borerider stiffness values have been changed and its effect combined with the manufacturing tolerances on the dispersion of 120 mm APFSDS projectile has been examined analytically 12,13 . The simulations showed that projectile with softer sabot front borerider has more effect on the dispersion and the gap between the projectile and gun bore caused the projectile to tilt its principal axis off the bore centreline resulting in variations in muzzle exit conditions.…”
Section: Introductionmentioning
confidence: 99%
“…General system design analyses with "knee" concept were given in [22,23], and usage of "knee" concept in information technologies was explained in [24,25], in chemical engineering in [26], and in projectile design in [27]. The experimental setup and the results of measurements of the 2 identical square grounding loops buried in a 2-layer soil (the one backfilled with bentonite suspension and the other conventional), presented in [11], were analyzed using the proposed method.…”
Section: Introductionmentioning
confidence: 99%